Pengaruh Pemasaran Media Sosial dan Kesadaran Merek Terhadap Minat Beli pada Konsumen Kopi Tuku di Kota Malang - M Muti Udin; Amelindha Vania (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of social media marketing and brand awareness on purchase intention among consumers of Toko Kopi Tuku in Malang City. A descriptive quantitative approach was employed, involving 160 respondents selected using purposive sampling. Data were collected through an online questionnaire and analyzed using the Partial Least Square (PLS) method with SmartPLS version 4.0 software. The findings reveal that social media marketing has a positive and significant impact on purchase intention, while brand awareness does not show a significant effect. These results highlight the importance of implementing effective social media marketing strategies to attract consumer interest, particularly by delivering informative and interactive content tailored to their needs.